2019
DOI: 10.1177/0145561319875663
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Temporalis Fascia and Transcanal Composite Chondroperichondrial Tympanoplasty Techniques

Abstract: The purpose of this study was to compare the success rates and hearing outcomes of transcanal composite chondroperichondrial cartilage graft with that of underlay temporal muscle fascia (TMF) graft for myringoplasty. In this retrospective study, the medical records of patients who underwent type 1 myringoplasty between September 2015 and February 2018 at Otorhinolaryngology Department of Erzurum Ataturk University were reviewed. Demographic properties, preoperative otological findings, preoperative pure ton au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Pre-operative AB-gap was 19.5 + 5dB and postop. AB-gap was19.8 + 4.8dB 9 , this study corelate with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Pre-operative AB-gap was 19.5 + 5dB and postop. AB-gap was19.8 + 4.8dB 9 , this study corelate with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results of no significant postoperative hearing difference were reported between fascia and perichondrium [6]. Although cartilage tympanoplasty might show a worse air-bone gap closure at high frequencies due to the graft's stiffness or mass effect [4], several studies had reported comparable hearing outcomes between fascia and cartilage [30][31][32][33].…”
Section: Plos Onementioning
confidence: 53%
“…Tympanic membrane closure rate and air bone-bone gap closure rates were statistically better in composite fascia cartilage grafting compared to fascia alone grafts. 16 In a prospective case series of 31 patients who used composite fascia cartilage graft using an endoscopic approach, Lou et al achieved a 90% tympanic membrane perforation closure rate and better air-bone gap closure rates when compared with post-operative audiometry findings. 17 Shekharappa et al in a study of 30 patients, achieved a perforation closure rate of 93 % and an airbone gap closure rate of 90% using cartilage-only grafting.…”
Section: Discussionmentioning
confidence: 99%